The disruptive impact of generative AI: A literature review - Gonçalves Oliveira Guedes, Amanda; Sobreiro, Vinicius Amorim (Revista Gestão da Produção Operações e Sistemas, 2025)
Purpose: This study aims to present a literature review on the dark side of generative artificial intelligence (GenAI), drawing on previously published research. Theoretical framework: Research addressing common perspectives on the already identified impacts of GenAI on human activities is limited in recent literature. Methodology/Approach: The study applies the five-step method for identifying research gaps proposed by Jabbour (2013), Seuring (2013), and Lage Junior and Godinho Filho (2010). Findings: The results indicate a consensus in the literature regarding the impacts of GenAI. Research, practical & social implications: The study suggests a common perspective concerning the effects of GenAI on the labour market. Originality/Value: This study contributes by addressing the negative impacts of GenAI based on existing literature.